Policy Analysis of the Merger of BAN PAUD PNF and BAN-S/M into BAN-PDM: Assessor's Perspective - Septy Rovana; Ahmad Suriansyah; Sulistiyana Sulistiyana (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze the implementation of the merger policy in the early transition phase by positioning assessors as key actors in the national education accreditation system. The study used a qualitative approach with a public policy study design through in-depth interviews and document analysis. The results indicate that, normatively, the BAN-PDM merger policy has the potential to improve bureaucratic efficiency, consistency of accreditation standards, and integration of quality assurance across levels. However, in the early stages of implementation, various challenges were still encountered, particularly related to assessor readiness and capacity, adaptation of cross-level accreditation instruments, clarity of governance, and resistance and anxiety from educational units acting as assessors. This study also identified urgent needs in the form of strengthening assessor training, developing guidelines and SOPs for instrument harmonization, establishing competency-based assessor teams, and ongoing monitoring and evaluation.